Lightning over voltage performance of 132kV GIS substation in Malaysia - Bakar, A.H.A.; Mokhlis, Hazlie; Ling, L.A.; Ping, H.W. (IEEE, 2010)
Over voltages are phenomena present in all networks. They can be created externally or internally. Over voltages which can appear on the system for which the equipments are intended to operate is the basis of the selection of the strength of the equipment known as Insulation Coordination especially for voltages less than 275kV. Recently a Gas Insulated Substation (GIS) in Kuala Lumpur undergone overhaul. A study was carried out to investigate the lightning over voltages that affect the GIS Substation. The objective of the study was to determine whether the withstand capability or Basic Insulation Level (BIL) was the cause of the fault occurring in the substation.